Implementing Learning-Based Models to Enhance Reading Comprehension Skills in Elementary School Students - Feni Febrianti; Muh Ainul Basyirah (Winaya Inspirasi Nusantara Foundation, 2022)
Background of the problem: Education enhances human quality in knowledge, attitudes, and skills. Purpose: This study aims to determine the impact of implementing the Problem-Based Learning (PBL) model on improving reading comprehension skills among fourth-grade students at SD Ampenan. Method: A quantitative approach with a quasi-experimental design and pretest-posttest control group model was used. The subjects were fourth-grade students divided into an experimental group, which received PBL treatment, and a control group, which used conventional learning methods. Reading comprehension tests were administered before and after the treatment. Result: Data analysis showed a significant improvement in reading comprehension skills in the experimental group compared to the control group. Implication: The practical and theoretical implications of this research provide insights into effective teaching strategies, potentially influencing practices in education, curriculum development, and instructional design.